Comparison of loose silk and tightenable polypropylene seton placement in treatment of complex anal fistula - Celik, Yahya; Zeki Buldanli, Mehmet (Annals of Medical Research, 2021)
Aim: Treatment of complex anal fistula is a challenging task due to the risk of recurrence and development of incontinence and there is no consensus over how to treat this condition. We aimed to compare the results in our patients whom we have applied loose silk or tightenable polypropylene seton.Materials and Methods: Demographic characteristics, duration of hospital stay, duration of operation, duration between two operations in patients requiring second operation, time to healing, recurrence, pain assessment by using Visual Analogue Scale (VAS) during follow-up exams and gas and/or stool incontinence of patients with complex anal fistula diagnosis who were treated by loose silk or tightenable polypropylene seton between March 2017 and March 2019 in our clinic were examined.Results: In this study, 81 (86.2%) male and 13 (13.8%) female patients with a total of 94 were included. In 58 (61.7%) of these patients polypropylene and in 36 (38.3%) silk seton was used. The mean age of the patients was 42.5±12.1 years. Mean follow-up was 17.2±6.5 months. Recovery time in polypropylene group (9.9±1.3 weeks) was shorter than silk seton group (12.7±2.7 weeks) (p0.001). Pain VAS average was higher in polypropylene group (6.3±0.9) compared to silk seton group (5.1±0.7) (p0.001). There was no significant difference between two groups for recurrence and incontinence.Conclusion: For the treatment of complex anal fistula, placement of tightenable polypropylene compared to loose silk seton has advantages such as shorter healing time and less need for second operation but it causes more pain during follow-up exams.